Effects of neuromuscular training on knee joint stability after anterior cruciate ligament reconstruction - Choi, Ho-Suk; Shin, Jun-Ho; Shim, Jae-Kwang (Journal of Physical Therapy Science, 2015)
[Purpose] This study examined the effects of neuromuscular training on knee joint stability after anterior cruciate ligament reconstruction. [Subjects and Methods] The subjects were 16 adults who underwent arthroscopic anterior cruciate reconstruction and neuromuscular training. The Lysholm scale was used to assess functional disorders on the affected knee joint. A KT-2000 arthrometer was used to measure anterior displacement of the tibia against the femur. Surface electromyography was used to detect the muscle activation of the vastus medialis oblique, vastus lateralis, biceps femoris, and semitendinosus before and after neuromuscular training. [Results] There was significant relaxation in tibial anterior displacement of the affected and sound sides in the supine position before neuromuscular training. Furthermore, the difference in the tibial anterior displacement of the affected knee joints in the standing position was reduced after neuromuscular training. Moreover, the variation of the muscle activation evoked higher muscle activation of the vastus medialis oblique, vastus lateralis, biceps femoris, and semitendinosus. [Conclusion] Neuromuscular training may improve functional joint stability in patients with orthopedic musculoskeletal injuries in the postoperative period.